Sistem Informasi Pelayanan Warga RW 01 Kelurahan Rawa Buaya Berbasis Website - Rizki Akbar; Esron Rikardo Nainggolan; Siti Nur Khasanah (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2019)
The process of managing data for residents in RW 01 RT 003 Kelurahan Rawa Buaya currently running, there are several identified problems, namely difficulties in finding data because it is still stored in the form of an agenda, making a cover letter that must take a long time because it is still manually recorded. The purpose of this thesis report is to design a citizen service information system using the waterfall method and for modeling the system using UML while the programming language uses PHP and for Database using MySQL. The results of this study indicate that the use of a citizen service information system can help the registration and data collection of residents in managing moving data and the process of making reports on monthly population and transparency in local RT finances as expected.